PERILAKU PENJAMAH MAKANAN DALAM PROSES PENGOLAHAN MAKANAN DI PONDOK PESANTREN ROUDLOTUN NASYIIN-MOJOKERTO TAHUN 2016 - Oktafia Purnama Lailiyah; Rusmiati .; Sri Mardoyo (GEMA LINGKUNGAN KESEHATAN, 2016)
Boarding school is a religious educational institution that has its own peculiarities and different from other institutions. Kitchen of a boarding school is a spot of food service for students. Cooking services has  not been managed and handled well by the food handlers that can cause foodborne illness. This study aims to determine the behavior of food handlers on food processing in Roudlotun Nasyiin boarding school Mojokerto regency. This is a descriptive study. Data collection techniques used questionnaires to food handlers in Roudlotun Nasyiin boarding school. The results of the study on 20 food handlers showed that 55%  food handlers in Roudlotun Nasyiin boarding school had good manner, 70% had good knowledge, 50% had  good attitude and 55% had a good action. Some suggestions taken from the result include the use of apron, mask, gloves, and food clamps in food processing to protect the food from contamination. The boarding school managers should send the food handlers to training in food hygiene sanitation conducted by the health department. The health of food handlers must be supervised with periodic examination of food handlers at least twice a year. Keywords: The Behavior, Food Handler, Food Processing